De-regulation of aurora kinases by oncogenic HPV; implications in cancer development and treatment - Kemi Hannah Oladipo; Joanna L. Parish (Tumour Virus Research)
Human papillomaviruses (HPVs) cause diseases ranging from benign warts to invasive cancers. HPVs are the cause of almost all cervical cancers and a sub-set of other epithelial malignancies including head and neck cancers, specifically within the oropharynx. The oncogenic properties of HPV are largely mediated through the viral oncoproteins E6 and E7, which disrupt many cellular pathways to drive uncontrolled cell proliferation. One family of proteins targeted by HPV is the Aurora kinase family. Aurora kinases are serine/threonine kinases including Aurora kinase A (AURKA), B (AURKB), and C (AURKC) which are often dysregulated in many cancer types, including HPV driven cancers. All three family members play essential roles in mitotic regulation and accurate cell division.The deregulation of Aurora kinases by HPV infection highlights their potential as therapeutic targets in HPV-associated malignancies. Targeting Aurora kinase activity, in combination with current HPV therapies, may provide new avenues for treating HPV-induced cancers and reducing the burden of HPV-related diseases. Combinatorial inhibition targets distinct but overlapping functions of these kinases, thereby reducing the potential for cancer cells to develop resistance. This broad impact emphasizes the capability for Aurora kinase inhibitors not only as anti-mitotic agents but also as modulators of multiple oncogenic pathways. This review explores the combinatorial effects of Aurora kinase inhibition, offering insights into novel therapeutic strategies for the treatment of HPV-driven cancers.